Analisis Penyerapan Tenaga Kerja Pada Industri Batu Bata di Kecamatan Seputih Mataram Kabupaten Lampung Tengah - Benny Prayudi; Ida Budiarty; irma febriana MK (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2019)
One of the efforts in job creation is to carry out development in the industrial sector. The industrial sector is theoretically believed to be the leading sector in the economy. The growth and development of the industrial sector mean more extensive opportunities to absorb labor. More labor absorption occurs in urban areas compared to rural areas. The difficulty of finding employment, lack of expertise, and low levels of education are reasons some villagers work in the brick industry. This type of production is more common in rural areas, given that one of the industrial raw materials, clay, is more easily obtained in rural areas. This study was conducted to determine the effect of wage variables, capital prices, and output levels on employment in the brick industry in the Seputih District of Mataram. The data used is sourced from primary data. Primary data was obtained by distributing questionnaires to brick entrepreneurs in the Seputih District of Mataram, Central Lampung Regency. Estimation results show these variables partially or jointly affect the absorption of labor by 88.75 percent. The effect of working capital growth on the growth of the intake of workers shows the highest coefficient. Thus a government guarantee is needed to increase working capital in the brick management business if the government wants to increase employment expansion.